Tożsamość młodzieży wietnamskiego pochodzenia w Republice Czeskiej - Kasprzak, Tomasz (Człowiek i Społeczeństwo, 2017)
The article presents an image of the identity of young Vietnamese living in the Czech Republic. After the dissolution of Czechoslovakia, most of the Vietnamese were left, and over time this minority started to grow (now they number more than 57,000 people). Multivariate social transformations, manifested in the continuous creation of the modern world, contribute to the difficulty of capturing and unambiguously identifying the notion of identity. Identity is primarily a social phenomenon, is closely related to values accepted in a given society, is present in its culture, and is strongly rooted in social consciousness. Multidimensional and multidimensional identity undoubtedly shapes the problem of self-awareness among Vietnamese youth.